USER FINANCIAL LITERACY LEVEL TOWARDS KREDIVO P2P LENDING SERVICES - Nurkamizah; Desca Wahyuni; Muhammad Fauzan (Indragiri Research Center (ingreat), 2025)
The development of financial technology, particularly peer-to-peer (P2P) lending services in Indonesia, is experiencing rapid growth, one of which is through the Kredivo platform, which offers easy access to digital-based credit. However, this convenience also has the potential to create financial risks if not balanced with an adequate level of financial literacy among its users. This study aims to determine and analyze the level of financial literacy of users regarding the Kredivo P2P lending service using quantitative methods through a descriptive approach. Data were collected through questionnaires distributed to Kredivo users and analyzed based on indicators of financial knowledge, risk understanding, financial attitudes, and financial behavior. The results show that the level of financial literacy of Kredivo users is in the moderate category, indicating that users have a basic understanding of P2P lending products, but still have limitations in understanding long-term risks and managing payment obligations. Therefore, efforts are needed to improve financial literacy education from service providers and regulators to minimize financial risks and improve consumer protection.